A framework for evaluating the impacts of reservoirs on seasonal ecohydrological conditions based on new eco‐flows. Issue 5 (26th March 2021) - Guo, Xiaoming; Guo, Yan; Xu, Lukai; Deng, Yu; Yang, Chaohui
Abstract: The eco‐flow metrics (ecosurplus [ES] and ecodeficit [ED]) based on flow duration curves (FDCs) are currently less popular than other metrics used to assess the ecohydrological conditions of rivers. To fully utilize their application potential, the seasonal ES and ED are redefined based on discharge hydrographs (DHs) rather than their FDCs. The annual ES and ED are redefined as the sum of the four seasonal ES and ED values, respectively. The impact of reservoirs can be measured by the rate of increase of the cumulative seasonal eco‐flows. Taking the seasonal EDs calculated by the 10% DH and 20% DH as the two threshold values, a risk evaluation method is proposed that classifies the seasonal ecohydrological conditions into four risk levels: no risk, low risk, moderate risk, and high risk. A daily discharge time series ranging from 1956 to 2015 in the Yellow River is used to perform a case study. The results showed that the Shannon diversity index ( H ) had a strong relevance to the annual ED. Riverine biodiversity was more sensitive to summer and autumn droughts than to floods. The Xiaolangdi Reservoir affected the seasonal eco‐flows much more than the Sanmenxia Reservoir. The winter season is currently classified as having a high risk and should be given more attention by river managers in the future. After the ecological regulation measures are implemented in the future to improve the winter conditions, their effects can be re‐evaluated by the above framework.